2008
DOI: 10.1146/annurev.matsci.38.060407.130315
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in Irradiation-Resistant Steels

Abstract: Advanced fission and future fusion energy will require new high-performance structural alloys with outstanding properties that are sustained under long-term service in ultrasevere environments, including neutron damage producing up to 200 atomic displacements per atom and, for fusion, 2000 appm of He. Following a brief description of irradiation damage and damage resistance, we focus on an emerging class of nanostructured ferritic alloys (NFAs) that show promise for meeting these challenges. NFAs contain an ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
643
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,094 publications
(678 citation statements)
references
References 124 publications
11
643
1
Order By: Relevance
“…[1][2][3][4][5] The widely practiced processing route for these ODS steels is essentially a two-step powder metallurgy process, consisting of mechanical alloying (MA) of 10-to 90-lm-diameter pre-alloyed Fe-based alloy powder together with a normally nano-sized (20 to 50 nm) Y 2 O 3 powder until fine-scale mixing/alloying is achieved, followed by consolidation of the powder into a bulk form typically by hot isostatic pressing (HIP) or related technique. [5][6][7][8][9][10] This MA approach is now well optimized and convenient for laboratory-based studies, providing good quality material sufficient for detailed microscopy, irradiation, and mechanical property assessment. However, in technological terms, disadvantages of the MA route include prolonged processing time, small batch size, tendency for contamination associated with the high specific area of the powder, and the high inherent cost of the pre-alloyed feedstock powders, which combine to restrict wider commercial implementation of the MA-based route.…”
Section: Ferritic Oxide Dispersion-strengthened (Ods)mentioning
confidence: 99%
“…[1][2][3][4][5] The widely practiced processing route for these ODS steels is essentially a two-step powder metallurgy process, consisting of mechanical alloying (MA) of 10-to 90-lm-diameter pre-alloyed Fe-based alloy powder together with a normally nano-sized (20 to 50 nm) Y 2 O 3 powder until fine-scale mixing/alloying is achieved, followed by consolidation of the powder into a bulk form typically by hot isostatic pressing (HIP) or related technique. [5][6][7][8][9][10] This MA approach is now well optimized and convenient for laboratory-based studies, providing good quality material sufficient for detailed microscopy, irradiation, and mechanical property assessment. However, in technological terms, disadvantages of the MA route include prolonged processing time, small batch size, tendency for contamination associated with the high specific area of the powder, and the high inherent cost of the pre-alloyed feedstock powders, which combine to restrict wider commercial implementation of the MA-based route.…”
Section: Ferritic Oxide Dispersion-strengthened (Ods)mentioning
confidence: 99%
“…These defects and flaws not only deteriorate the physical properties of materials but also cause direct structural failure [7]. Compared with the conventional polycrystalline materials, nanocrystalline materials exhibit the superior property of radiation resistance due to the significantly decreased grain size and the increased volume fraction of grain boundary (GB) [1,2,8,9]. It has been demonstrated that grain boundary can act as an efficient sink for reducing the accumulation of radiation defects in nanocrystalline metals [10][11][12][13], alloys [14,15], and oxides [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Oxide nanoparticles also provide a high density of sinks for irradiation induced point defects and He. This would reduce irradiation hardening and restrain the formation of He bubbles at grain boundaries, preventing embrittlement [6,7].…”
Section: Introductionmentioning
confidence: 99%